Composite bone cements for hyperthermia: modeling and characterization of magnetic, calorimetric and in vitro heating properties. Issue 6 (15th April 2017) - Miola, Marta; Laviano, Francesco; Gerbaldo, Roberto; Bruno, Matteo; Lombardi, Alberto; Cochis, Andrea; Rimondini, Lia; Verné, Enrica
Abstract: Composite bone cements, based on commercial polymethylmethacrylate, loaded with ferrimagnetic and bioactive glass-ceramic particles, were prepared and characterized. The characterization included: the evaluation of hysteresis losses in quasi static conditions, the quantification of specific power losses by calorimetric tests, optimization of experimental heating curve for hyperthermia treatment, confirmed by a theoretical model developed with Comsol Multiphysics ®, biological evaluations after magnetic induction heating using both tumoral osteosarcoma cells and not tumoral fetal osteoblast cells, and the evaluation of setting time. All the samples confirmed the ability to generate a hysteresis area, both at low and high external magnetic field, proportionally to the amount of magnetite, which is strictly correlated to calorimetric measurements. The heating generation of the sample was evaluated and controlled with two different methods and the results were comparable. The preliminary cellular heating tests revealed a selective tumoral cell death induced by the use of a suitable alternate magnetic field.